Optimalisasi FoMO dalam Copywriting PAS dengan Pemanfaatan Cinta Tanah Air - Rolan Mart Sasongko; Rifky Adiyatna, Hafidh; Saraswati, Yudhistira (Institut Teknologi dan Bisnis Semarang, 2023)
This research discusses the training of copywriting training and its impact on increasing sales of MSME products in Yogyakarta City. Yogyakarta. This training aims to improve participants' skills in producing effective copywriting that attracts consumers' attention. The training method involved the delivery of materials by the instructor on the importance of copywriting, techniques for creating attractive copywriting, and strategies to utilize the to utilize the